Nitrogen Response of Barley in Dolakha district, Nepal - Baral, Bandhu Raj; Nepali, Dinesh (Journal of Nepal Agricultural Research Council, 2025)
Barley is the fifth most important cereal crops of Nepal and serves as the staple food of high hill people.The low productivity of barley in Nepal is largely associated with improper nutrient management. A field experiment was conducted to study the response of six different nitrogen doses on barley variety ‘Muktinath Jau’ at Hill Crops Research Program (HCRP), Kabre, Dolakha during 2022 and 2023. The field experiment consists of six nitrogen levels (0, 30, 60, 75, 90 and 105 kg/ha) as treatments replicated four times and laid out in randomized complete block design. The results revealed that the plant height, days to maturity, number of tillers per m2, spike length, grain yield, and straw yield were significantly influenced by nitrogen doses. The highest grain yield (2.85 t/ha) was produced at 90 kg N/ha and did not significantly differ with 75 kg N/ha and 105 kg N/ha. The results clearly indicated that 75 kg N/ha could be optimum in Kabre station of Dolakha district and in areas with similar soil types and climate of Nepal.